Strategic decision through integrated marketing communication and strategy analysis for Siakad Mataer digital platform - Dini Fallah; Pri Hermawan (Priviet Social Sciences Journal, 2026)
This study examines how PT Mataer Digital Nusantara (MDN) can strengthen its marketing strategy and integrated marketing communication to overcome inconsistent client acquisition for its SIAKAD 4.0 platform in Indonesia’s higher education sector. A mixed-method case study approach is employed, combining primary internal data from interviews and Likert-scale surveys involving employees in marketing, sales, product, and client management, with secondary data from PDDIKTI, government regulations, market reports, and competitor documents. Internal conditions are analyzed using segmentation–targeting–positioning (STP) and the 7Ps marketing mix, while external factors are evaluated through PESTLE and competitor analysis. The results are synthesized into a SWOT framework and further developed into strategic alternatives using the TOWS matrix. To ensure objective prioritization, a Weighted Scoring Model is applied as a multi-criteria decision-making tool. The findings reveal that MDN’s strengths include competitive pricing, platform credibility, and strong cross-functional execution, while weaknesses lie in limited segmentation adaptability and inconsistent strategic evaluation. The recommended strategy focuses on expanding market penetration among small- and medium-sized institutions through flexible pricing aligned with national digitalization trends, supported by trust-building communication. The study concludes with an actionable roadmap covering pricing strategies, segmentation redesign, product enhancement, onboarding processes, digital marketing, and performance evaluation systems.